Enhancing Conceptual Understanding in Geometry through Journal Writing: A Case from One Philippine Secondary School (American Journal of Interdisciplinary Research and Innovation, 2025)
Traditional assessment practices in Mathematics often stress procedural recall over conceptual understanding, limiting students’ opportunities for reflective engagement with abstract ideas. Reacting to this concern, the present study examined the effectiveness of journal writing as an alternative assessment tool for promoting students’ understanding of Geometry concepts. Anchored on constructivist and metacognitive learning perspectives, a quasi-experimental pretest–posttest design was employed with two intact Grade 10 classes from a public secondary school in South Cotabato, Philippines. The experimental group utilized journal writing to record reasoning processes, reflections, and conceptual insights, while the control group was assessed using conventional paper-and-pencil tests. Data were gathered through validated pretests and posttests as well as open-ended questionnaires. Quantitative results indicated that the experimental group got significantly higher mean gain scores than the control group, showing the positive impact of journal writing on students’ conceptual growth. Thematic analysis of qualitative responses further disclosed that journal writing improved learners’ comprehension of geometric principles, sustained memory retention, and promoted reflective thinking. Taken together, these findings present empirical proof that journal writing constitutes a meaningful mode of alternative assessment, augmenting traditional measures and encouraging deeper engagement in Mathematics classrooms